Intrauterine Fetal Surgery Current Approaches - Ayla Eser; Nermin Köşüş; Aydın Köşüş; Müberra Namlı Kalem; Nilüfer Akgün; Ebru Yüce (Gynecology Obstetrics & Reproductive Medicine)
Though prenatal diagnosis has advanced a lot along with surgical techniques, intrauterine fetal surgery often not the preferred option. This is because the risks involved for both the mother and the fetus during and after the operation are often much more than the benefit to be achieved. Moreover, the infrastructure require ments and the costs of such operations are quite high. Fetal intervention is only possible in circumstances where the operation will correct abnormalities of the fetus which hamper normal growth, thus enabling normal fetal development (Twin-to-twin transfusion syndrome, congenital diaphragmatic hernia, Space-occupying thoracic lesions, Obstruction of lower urinary tract ect). It is mainly indicated in diseases that can result in intrauterine fetal death or whose effects could not be corrected postnatally (congenital aortic valve stenosis, hypoplastic left heart syndrome ect.). The proven pathophysiology and proper identification of the defect or disease is thus necessary before attempting such intervention. Since intrauterine fetal surgery entail high risks for both the fetus and the mother, there are ethical controversies regarding research in fetal surgery. Suitable surgical techniques, appropriate and effective high end methods to monitor fetal and uterine development and prevention of uterine contractions after surgery (tocolysis) are a few of the key bottlenecks that need to be addressed urgently to make intrauterine fetal surgery more useful. This article reviews recent intrauterine fetal interventions and their risk and success rates.